Differential effects of single versus combined cognitive and physical training with older adults: The SimA study in a 5-year perspective - Oswald, Wolf Dieter; Gunzelmann, Thomas; Rupprecht, Roland; Hagen, Bernd (European Journal of Ageing, 2006)
The present study evaluates the effect of cognitive training, of psychoeducational training and of physical training on cognitive functioning, physical functioning, physical health, independent living and well-being in older people. Also the combination of physical training with cognitive training or psychoeducational training, respectively, was evaluated. In contrast to most training studies with older people, training effects were evaluated in a longitudinal perspective over 5 years to analyse long-term-results of cognitive and physical activity on older adults. Training effects were evaluated compared to a no-treatment-control group. Subjects were 375 community residents aged 75-93 years. Up to 5 years after baseline examination, significant training effects were observed in the group exposed to the combined cognitive and physical training. The physical and cognitive status in the participants of this group could be preserved on a higher level compared to baseline, and the participants displayed fewer depressive symptoms than the no-treatment-control group. The results are discussed in the light of recent research regarding the effects of mental and physical activity on brain function in older adults. © Springer-Verlag 2006.
Keywords: Cognitive training; Physical training; Independent living; Dementia